Особенности расчета вероятности разрушения резца с круглой пластиной - Девин, Л.Н.; Сулима, А.Г. (Породоразрушающий и металлообрабатывающий инструмент – техника и технология его изготовления и применения, 2008)
The stress and reliability of the diamond cutting tools during Si-Al alloys machining were investigated at the beginning of cutting. The basic influence of stress deviations on reliability of cutting was shown.